Pola asuh ibu dan peran teman sebaya pada perilaku pacaran remaja - Novi Berliana; Sumarni Sumarni; Idei Khurnia Swasti (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Maternal pattern and the role of peers in high school youth dating behavior in JambiPurposeThe purpose of this paper was to determine the relationship between parental parenting and the role of peers with youth dating behavior in Jambi. MethodA cross-sectional study was conducted involving 281 students of SMAN 4 and SMAN 11 in Jambi who were or have been dating. Data were analyzed using univariate, bivariate with chi square tests, and multivariate with logistic regression tests.Results281 respondents, 113 (72.44%) of the majority of male adolescents behaved in risky courtship. Bivariable analysis found that there was a significant correlation between the role of peers and teenage dating behavior, while the relationship of mother pattern with teenage dating behavior was found to be insignificant. Multivariable analysis, obtained the result that the role of peers is the dominant variable associated with youth dating behavior with OR 2.74 times (95%, CI = 1.61-4.67). ConclusionThis study contributes to the knowledge that a poor peer role for adolescents has a risk to behave in risky dating and mother's parenting does not have a meaningful relationship with youth courtship behavior.